Pengaruh Kerjasama Tim, Motivasi Kerja, Dan Disiplin Kerja Terhadap Kinerja Karyawan Rekammedis Rsud Dr. Haryoto Lumajang - Abdillah, Mohammad Rifki; Djaelani, Abdul Kodir; Novianto, Abdullah Syakur (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study is to ascertain how the performance of medical records staff members at RSUD Dr. Haryoto Lumajang is impacted by collaboration, work motivation, and work discipline. This research uses quantitative methods with multiple linear regression analysis techniques. The respondents in this study were all medical records employees at Dr. Haryoto Lumajang with a total of 36 people. Respondents were selected using a saturated sampling technique. Data were collected using a questionnaire consisting of three independent variables, namely Teamwork, Work Motivation, and Work Discipline and one dependent variable, namely Employee Performance. SPSS (Statistical Program for Social Science) was used to examine the data. The study's findings show that cooperation has no appreciable impact on the performance of medical records employees at Dr. RSUD. Haryoto Lumajang, Work Motivation has a significant effect on the Performance of Medical Record Employees at Dr. RSUD. Haryoto Lumajang, and Work Discipline has a significant effect on the Performance of Medical Record Employees at Dr. RSUD. Haryoto Lumajang. Keywords: Medical Records, Employee Performance, Work Discipline, Teamwork, Work Motivation